APPLICATION OF COOPERATIVE LEARNING TYPE PICTURE TO PICTURE TO INCREASE STUDENT’S COMPREHENSION ON SOCIAL STUDIES - Deden Herdiana Altaftazani (IKIP Siliwangi, 2018)
This research is based on the result of observation in the fourth grade students SDN Taman Kopo Indah. When learning activities take place, Researchers found the various problems. These problems lead to low comprehension of students. This study aims to determine Whether students' comprehension can improve After the implementation of model cooperative learning type picture to picture in social science learning. The research method used is Classroom Action Research Which refers to the Kemmis and Mc Taggart models. This research is done with the stages of planning, implementation, observation, and reflection. This study was conducted in 3 action cycles. The results obtained are: The average percentage of students' complete mastery in the first cycle of 45%, In the second cycle increased by 35% to 80%, And cycle III increased by 5% to 85%. so, it is recommended for teachers to implement cooperative learning model type of picture to picture in the social science learning.